Comportamento de poedeiras criadas a diferentes densidades e tamanhos de grupo em ambiente enriquecido - Pereira, Danilo Florentino [UNESP]; Batista, Edna dos Santos [UNESP]; Sanches, Filipe Teixeira [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Bueno, Leda Gobbo de Freitas [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of this work was to determine the behavioral differences among laying hens reared at different densities and group sizes, in an enriched environment. Isa Brownlaying hens with ages from 30 to 32-week-old, in small-sized and deformed pens, were used. Hens were raised during 28 days in bays with shavings bedding, perch and nest. Two group sizes were evaluated (6 and 12 fowls) and at two rearing densities (774 and 1,440 cm2 by fowl) in a factorial arrangement with three replicates. In fifteen-minute video footages, it was recorded the frequency and the expression period for the following behavior were recorded: feather scratching, sand bath, wing beating, drinking water, pecking, head scratching, earth scratching, eating, perching, leg stretching, pursuing, sitting, and nest visiting. The treatments and the interaction between them had significant effects. The six-hen group increased the frequency of behavior types that indicate fowl frustration, regardless of density. The group size is the most important factor for hen well-being.

O objetivo deste trabalho foi determinar diferenças comportamentais entre poedeiras criadas sob diferentes densidades e tamanhos de grupo, em condições de ambiente enriquecido. Foram utilizadas poedeiras Isa Brown com idade entre 30 e 32 semanas alojadas em galpões de escala reduzida e distorcida. As aves foram criadas durante 28 dias, em baias com cama de maravalha, poleiro e ninho. Foram avaliados dois tamanhos de grupos (6 e 12 aves) e duas densidades de criação (774 e 1.440 cm² por ave), em arranjo fatorial com três repetições. Em amostras de vídeo de 15 min, foram registrados as frequências e os tempos de expressão dos comportamentos: arrumar penas, banho de areia, bater asas, beber água, bicar, coçar a cabeça, ciscar, comer, empoleirar, esticar perna, perseguir, sentar e visitar o ninho. Foram observados efeitos significativos dos tratamentos e da interação entre eles. O grupo de seis aves manifestou aumento da frequência de comportamentos que indicam maior frustração das aves, independentemente da densidade. O tamanho de grupo é o fator mais importante para o bem-estar das aves.
Behavior of hens reared at different densities and group sizes in an enriched environment
Keywords: Animal welfare; Ethology; Farming systems; Precision animal production.